How Deep Is Your Care? Analysis of Corporations’ “Caring Level” and Impact on Earnings Volatility from the Ethics of Care Perspective - Desi Adhariani; Sylvia Veronica Siregar (Australasian Accounting, Business and Finance Journal, 2019)
Corporate failures and unethical conduct of business indicate the value of business ethics to protect stakeholders’ interests. This research is aimed at assessing the level of caring principles exercised by companies in Indonesia and investigating the impact of caring behaviour on the earnings volatility. The caring principles emphasise building good relationships with stakeholders including in conflict resolutions. Assessment of the caring principles is conducted through analysis of disclosures using the matrix approach of content analysis for information provided in the Annual Report and Sustainability Report in the period 2012-2016. The ethics of care is the underlying theory of this research, from which the caring principles were developed. The results show that the caring level assessed from disclosures is still low, but there is an increasing trend of disclosures in the five-year period, representing ample room for improvement in the ethical practices and related disclosures. Furthermore, in line with the hypothesis, the caring practices measured in the disclosures are found to lower the earnings volatility. This study contributes to the literature of business ethics, especially the ethics of care, by offering the assessment of corporate caring level through disclosures. The practical implication of the study is expected to raise awareness of the importance to be more caring in conducting business as it can support companies in maintaining the level of stable earnings.
Keywords: Caring; ethics of care; content analysis; earnings volatility.